2013
DOI: 10.1038/emboj.2013.118
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic regulator PLZF represses L1 retrotransposition in germ and progenitor cells

Abstract: Germ cells and adult stem cells maintain tissue homeostasis through a finely tuned program of responses to both physiological and stress-related signals. PLZF (Promyelocytic Leukemia Zinc Finger protein), a member of the POK family of transcription factors, acts as an epigenetic regulator of stem cell maintenance in germ cells and haematopoietic stem cells. We identified L1 retrotransposons as the primary targets of PLZF. PLZFmediated DNA methylation induces silencing of the full-length L1 gene and inhibits L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 58 publications
3
62
0
Order By: Relevance
“…A gain-of-function mutation of Plzf has been found to enable mouse BM cells to increase their self-renewal capacity (40), similarly to in our previous study (10), but the molecular mechanism is poorly understood. In the present study, we found induction of Eya2 expression by transduction of PLZF-RARA and rapid and dose-dependent reduction of Eya2 following degradation of PLZF-RARA by ATRA, as well as upregulation of Eya2 through promoter binding by Plzf.…”
Section: Discussionsupporting
confidence: 74%
“…A gain-of-function mutation of Plzf has been found to enable mouse BM cells to increase their self-renewal capacity (40), similarly to in our previous study (10), but the molecular mechanism is poorly understood. In the present study, we found induction of Eya2 expression by transduction of PLZF-RARA and rapid and dose-dependent reduction of Eya2 following degradation of PLZF-RARA by ATRA, as well as upregulation of Eya2 through promoter binding by Plzf.…”
Section: Discussionsupporting
confidence: 74%
“…Taken together, these results explain how PLZF alone can function at different levels to recruit a broad effector gene program. Although PLZF contains nine zinc fingers at its carboxy terminus, some of which have been proposed to bind DNA in a sequence-specific manner in myeloid cell types, ChIP-seq analyses have not been reported, and a consensus binding sequence has not emerged (32)(33)(34)(35)(36). Our study suggests the possibility that rather than binding a specific consensus motif, PLZF may occupy regulatory regions associated with other canonical lymphoid transcription factors, such as ETS, E protein, and RUNX.…”
Section: Discussionmentioning
confidence: 75%
“…Among the best characterized putative PLZF targets is Kit, which encodes a type-III receptor tyrosine kinase required for spermatogonial differentiation (Besmer et al, 1993;Dym et al, 1995;Koshimizu et al, 1992 Zhang et al, 2011). Previous studies demonstrated weak PLZF interaction with the Kit promoter by ChIP in enriched populations of mouse spermatogonia and the activation of Kit mRNA in Plzf mutants (Filipponi et al, 2007;Hobbs et al, 2012;Puszyk et al, 2013), which led to the conclusion that PLZF directly represses Kit transcription. We detected a shared binding site in the first intron of Kit (active region 17206, Table S2), yet we did not find any evidence of PLZF binding to the Kit promoter in THY1 + spermatogonia.…”
Section: Discussionmentioning
confidence: 99%